Skilled labour and professionalism in Ancient Greece and Rome - Harris, Edward 1951- (Cambridge University Press, 2020)
This book is a history of ancient Greek and Roman professionals: doctors, seers, sculptors, teachers, musicians, actors, athletes and soldiers. These individuals were specialist workers deemed to possess rare skills, for which they had undergone a period of training. They operated in a competitive labour market in which proven expertise was a key commodity. Success in the highest regarded professions was often rewarded with a significant income and social status. Rivalries between competing practitioners could be fierce. Yet on other occasions, skilled workers co-operated in developing associations that were intended to facilitate and promote the work of professionals. The oldest collegial code of conduct, the Hippocratic Oath, a version of which is still taken by medical professionals today, was similarly the creation of a prominent ancient medical school. This collection of articles reveals the crucial role of occupation and skill in determining the identity and status of workers in antiquity
Title from publisher's bibliographic system (viewed on 21 Sep 2020)
Keywords: Skilled labor / Greece / History / To 146 B.C.; Skilled labor / Rome / History; Fachkraft; Professionalität; Antike; Römisches Reich; Griechenland -- Altertum